2(-5y-7)+7y=-8

Simple and best practice solution for 2(-5y-7)+7y=-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-5y-7)+7y=-8 equation:


Simplifying
2(-5y + -7) + 7y = -8

Reorder the terms:
2(-7 + -5y) + 7y = -8
(-7 * 2 + -5y * 2) + 7y = -8
(-14 + -10y) + 7y = -8

Combine like terms: -10y + 7y = -3y
-14 + -3y = -8

Solving
-14 + -3y = -8

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + -3y = -8 + 14

Combine like terms: -14 + 14 = 0
0 + -3y = -8 + 14
-3y = -8 + 14

Combine like terms: -8 + 14 = 6
-3y = 6

Divide each side by '-3'.
y = -2

Simplifying
y = -2

See similar equations:

| 79=5x+3(x-3) | | X-17=4x+1 | | 6e+2=2e+5 | | z^3-3z^2+(1+3i)z-6i+2=0 | | 2x-5=3x+18-5 | | 2x-2=8x | | x^2=5+2x | | 6x+1+7x-9=180 | | -3y=-6-x | | Y=5x^2+10x+3 | | -9x=20+4y | | (x+3)*(x-1)-(x-3)*(x+2)=15 | | 3m+2n=p | | 2(q+3)=16 | | 3x+8+2y=1 | | 0=40-2x-10y | | 5(y-1)=2y+7 | | 7*(2x+5)=4x-9-x | | 2(-y-1)-y=-5 | | -6k-13+13=83+13 | | 7*2x+5=4x-9-x | | 90+x+46+x+56=180 | | m+(-6)=2 | | 3+5x=0 | | 4x+9+3x+19+75=180 | | 5m-20=3m | | D=100-6P | | 3(3y+4)+y=4 | | -8-2f=8-6f | | x^2+110x+2000=0 | | -6q=q-7q | | (x+2)+(2x-3)=180 |

Equations solver categories